2014
DOI: 10.4187/respcare.03553
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Need for Noninvasive Ventilation During Respiratory Tract Infections in Medically Stable, Non-Ventilated Subjects With Amyotrophic Lateral Sclerosis

Abstract: BACKGROUND: Acute lower respiratory infections can impair muscle strength in patients with amyotrophic lateral sclerosis (ALS). When associated with an increase in load on the respiratory system, this situation may precipitate hypercapnic respiratory failure in non-ventilated patients with ALS. The aim of this study was to determine whether a clinical or functional parameter can predict the need for noninvasive ventilation (NIV) during an acute respiratory infection for medically stable, non-ventilated patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…Our data further showed that the PCF, as measured 5.6 weeks before the first HVS assessment, was the only test that discriminated ‘NIV indication’ from ‘no NIV indication yet’ patients. A predictive value of PCF for the need for NIV has been found previously in patients with ALS who had an acute lower respiratory tract infection [16]. Together, our findings and previous findings by others suggest the value of PCF, which should lead to more frequent use of this measure during the respiratory care of patients with ALS [2931].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our data further showed that the PCF, as measured 5.6 weeks before the first HVS assessment, was the only test that discriminated ‘NIV indication’ from ‘no NIV indication yet’ patients. A predictive value of PCF for the need for NIV has been found previously in patients with ALS who had an acute lower respiratory tract infection [16]. Together, our findings and previous findings by others suggest the value of PCF, which should lead to more frequent use of this measure during the respiratory care of patients with ALS [2931].…”
Section: Discussionsupporting
confidence: 85%
“…Peak cough flow (PCF) estimates cough efficacy and airway clearance and may help decisions regarding cough augmentation. The role of PCF in predicting the need for NIV is not yet fully clarified [1416]. Furthermore, the maximum inspiratory and expiratory pressures (MIP and MEP) may have a higher sensitivity for nocturnal hypoventilation compared to the FVC in patients with ALS [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…We have used VC-CMV with our patients for a number of years. We have previously studied various aspects of this procedure, 29 and we have compared our results with those of a group with expertise in PC-CMV who take a similar approach to ours with regard to respiratory secretion management. 8 From an ethical standpoint, the procedure we use with our patients must be the one in which we have the most expertise; therefore, we acknowledge possible limitations in our method, most notably the lack of a control group.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of RESPIRATORY CARE, Sancho et al 1 describe a prospective study of medically stable subjects with amyotrophic lateral sclerosis (ALS) to determine possible clinical or functional predictors of need for noninvasive ventilation (NIV) during an acute lower respiratory tract infection. They used the criteria of the American College of Chest Physicians 2 to initiate NIV at home.…”
mentioning
confidence: 99%
“…The decision to initiate NIV has some variability, as previously cited in the literature. 3 When analyzed with respect to current NIV guidelines, almost all subjects in the Sancho study 1 should have been receiving NIV because they presented with an FVC of Ͻ 75% of predicted and a maximum inspiratory pressure of more than Ϫ60 cm H 2 O. Some ALS centers currently consider, in addition to these criteria, the presence of signals/symptoms of respiratory insufficiency.…”
mentioning
confidence: 99%